Body Mass Index, Gestational Weight Gain, and Obstetric Complications in Moroccan Population - Latifa Mochhoury; Rachid Razine; Jalal Kasouati; Mariam Kabiri; Amina Barkat (Hindawi Limited, 2013)
Objectives. To evaluate the impact of the body mass index (BMI) before pregnancy and the weight gain during pregnancy, on the occurrence of maternal and neonatal morbidity in the Moroccan population, as well as to analyze the quality of the weight gain depending on the BMI. Methods. A study was carried out over a period of one year from October 1, 2010 to October 1, 2011, using data collected from a descriptive-transversal study. We recruited nondiabetic women without several HTAs, delivering singletons from 37 completed weeks up to 42 weeks gestation. Results. Total of 1408 were analyzed. The risks of moderate hypertension, macrosomia, dystocia, and resort to cesarean section were higher among overweight or obese women, as well as among women whose weight gain was >16 kg. The differences were significant <0.05. Conclusion. This study demonstrates that overweight women before pregnancy and weight gain during pregnancy are associated with higher risks of maternal and neonatal complications. These data provide ideas on prevention opportunities.